A mitochondria-targeting fluorescent Fe3+ probe and its application in labile Fe3+ monitoring via imaging and flow cytometry. (October 2018) - Zhu, Chengcheng; Wang, Mengjia; Qiu, Lin; Hao, Shuangying; Li, Kuanyu; Guo, Zijian; He, Weijiang
Abstract: The biogenesis of heme and iron-sulfur cluster in mitochondria is closely associated with the intracellular iron homeostasis. In this study, a mitochondria-targeting probe with the reversible turn-on fluorescent response to Fe 3+ was developed for mitochondrial labile Fe 3+ monitoring by modifying spirolactam rhodamine with a chelator. With this probe, the mitochondrial labile Fe 3+ fluctuation in adherent cells upon ferric citrate incubation was visualzied via confocal imaging, and the flow cytometric assay for mitochondrial Fe 3+ in suspension cells, which is difficult to be monitored via confocal imaging, was also developed. Moreover, the labile Fe 3+ drop in mitochondria of K562 cells undergoing the DMSO-stimulated erythroid differentiation was observed for the first time. Graphical abstract: The newly developed mitochondrion-targeting fluorescent probe of the reversible turn-on response to Fe 3+, Mito-RhFe, enables the fluorescence imaging and flow cytometry for mitochondrial labile Fe 3+ in live cells, and the DMSO-stimulated erythroid differentiation of K562 cells was disclosed with the drop of mitochondrial labile Fe 3+ . Highlights: A mitochondria-targeting probe of reversible turn-on fluorescent response to Fe 3+ was developed. The labile Fe 3+ drop in mitochondria in the stimulated erythroid differentiation of K562 cells was disclosed. Imaging and flow cytometry for mitochondrial Fe 3+ were realized respectively in adherent and suspension cells.